The effect of branching on the structure of confined thin films of alkanes - Dijkstra, Marjolein (Institute of Physics, 1997)
We report computer simulations in the grand canonical ensemble of a system of several linear and branched alkanes between two solid surfaces. We computed the solvation force exerted by the °uid on the plates. The solvation force for linear decane oscillates with distance with a periodicity close to the width of the molecules. The branched alkanes (2-methylundecane and 2-methylheptane) show a similar oscillatory behaviour; however, the oscillations are decreased and are shifted to the attractive regime.
Keywords: Natuur- en Sterrenkunde